(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to determine the Influence of Product Innovation and Store Atmosphere on Purchase Decisions of Fore Coffee Gayamsari Products in Semarang City with Purchase Interest as an Intervening Variable. The population used in this study were Fore Coffee Consumers and the sample used was 210 Fore Coffee Gayamsari consumers using AMOS 22. These results indicate that there is a positive and significant influence of product innovation on purchasing decisions with a P-value of 0.026 <0.050, store atmosphere has no positive and insignificant effect on purchasing decisions with a P-value of 0.082>0.050, purchase interest has a positive and significant effect on purchasing decisions with a P-value of 0.006 <0.050, Product Innovation has a positive and significant effect on purchase interest with a P-value of 0.025 <0.050, store atmosphere has a positive and significant effect on purchase interest with a P-value of 0.000 <0.050. Product innovation does not influence purchasing decisions mediated by purchase interest because the value of purchase interest to purchase decision (0.100) is greater than the influence of product innovation on purchase decision through purchase interest (0.026) and store atmosphere does not influence purchasing decisions mediated by purchase interest because the value generated by purchase interest to purchase decision (0.100) is greater than the influence of store atmosphere on purchase decision through purchase interest (0.070).